SAT0573 The Prevalence and Incidence of Systemic Lupus Erythematosus in Northern Italy: an Epidemiological Study Conducted with the "CAPTURE-RECAPTURE" METHODOLOGY. (23rd January 2014) - Tsioni, V.; Frassi, M.; Andreoli, L.; Allegri, F.; Airò, P.; Tincani, A.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease with multiple clinical presentations. Therefore, the correct clinical identification of SLE patients (Pts) may be an obstacle to epidemiological studies. In addition, the type of methodology applied to epidemiological research may greatly affect the results. In Italy, two epidemiological studies in SLE have been carried out. The first during the year 2002 in Florence, based on the registries of general practitioners (GPs). A Lupus Screening Questionnaire was administered by the GPs to screen Pts for SLE. The overall rate of SLE prevalence (P) was calculated as 71/100.000 adults (CI 49-92). The second study was carried out in Ferrara. Pts with SLE were identified by the international classification of disease code in the hospital discharge records. The P was calculated as 57.9/100.000 (CI 49-65) for the period 1996-2002 and the annual incidence (I) for 2000-2002 was estimated at 1.91/100.000 (CI 1, 45-2, 37). Our study was aimed at reassessing the P and I of SLE in Italy ten years after the first reports. In addition, we applied for the first time the capture-recapture (CR) methodology for estimating the size of the target population. Objectives: To investigate the P of SLE during the year 2011 and the I for the period 2009-2011 in the area of Valtrompia in Italy. Methods: Pts were recruited from two sources: 1) the records of 49/70 GPs in the area (70% of response), whose practices covered 67.615 individuals aged over 14 years; 2) the database of the main public hospital, where the only Rheumatology Unit of the area is located. The data from the two sources were analysed with the CR method. Results: By matching the two sources, a total of 25 Pts (4 males, 21 females) were identified: 23 from GPs records, 24 from the hospital database; 22 pts were retrieved by both sources. After written informed consent, all the Pts underwent a clinical evaluation by a rheumatologist of the hospital to confirm the diagnosis of SLE (at least 4 of the American College of Rheumatology Criteria). By applying the CR analysis, we calculated the equation of Chapman and the estimated number of pts resulted to be 25.1. P of SLE was estimated at 40.5 cases among 100.000 individuals aged over 14 years of age (CI:24.6-56.3). Between January 1, 2009 and December 31, 2011, 4 new cases of SLE were diagnosed, with annual crude I rate of 2.14/100.000. Conclusions: This is the third epidemiological study on SLE in Italy, but the first one to apply the CR analysis. This methodology allows to calculate the number of Pts by combining the number of Pts identified from multiple sources with the estimated number of "missed" pts. The area of Valtrompia consists in a 40 km long alpine valley, whose southern and only way-out corresponds to the main city where the only public Rheumatology Unit of the area is located. In addition, the close collaboration established with local GPs turned out in high rate of responses (70%). We found SLE P and I to be on line with the data from other European countries. The P in our study was lower than in the previous two Italian studies, but such a discrepancy can be explained by the different epidemiological methodologies. Disclosure of Interest: None Declared